Universities and Reflexive Modernity : Institutional Ambiguities and Unintended Consequences - Vlasceanu, Lazar (Book collections on Project MUSE., 2009)
A book about the challenges and uncertainties facing today's university, a chronicle of recent and current changes in higher education in the world. There are many questions today that are sufficiently open to doubt and profoundly related to new developments, to justify our starting new enquiries, here and now, by looking freshly and more closely at the actual configurations and at their historical grounds, for providing the new standard account of the university today. Vlasceanu discusses the inherent contradiction between academia on the one hand, and expectations and regulations of the marke.